11(n-3)=-4

this is also for my friend

Asked 8 months ago
Viewed 162851 times
1
11(n-3)=-4

this is also for my friend

2 Answer

2

Answer:

Step-by-step explanation:

Edit
avatar
Alphonso Conroy
15.5k 3 10 26
answered 8 months ago
2

Answer:

Step 1: Simplify both sides of the equation.

11(n−3)=−4

(11)(n)+(11)(−3)=−4(Distribute)

11n+−33=−4

11n−33=−4

Step 2: Add 33 to both sides.

11n−33+33=−4+33

11n=29

Step 3: Divide both sides by 11.

11n

11

=

29

11

n=

29

11

Answer:

n=

29

11

Step-by-step explanation:

Edit
avatar
Edward Glover
15.5k 3 10 26
answered 8 months ago